Meningkatkan Kinerja Melalui Semangat Kerja Dan Sistem Informasi Manajemen Di Toko Queen Bakery - Juliatin, Arin; Fitria, Ida Jalilah (STIM-LPI Makassar, 2024)
This research aims to explore ways to improve performance at the Queen Bakery store through increasing employee morale and using a more effective management information system. In this research, an analysis was carried out of the factors that influence employee morale and its impact on their performance. It also identified deficiencies in the use of computerized management information systems in Queen Bakery stores. The research results show that high work morale has a positive influence on employee performance at Queen Bakery. Employees who have high work morale tend to be more productive, produce better quality work, innovate, attend consistently, and have good working relationships with coworkers. However, there are signs of a lack of morale at the Queen Bakery store, even though the company has provided incentives to employees. Apart from that, it was also found that the Queen Bakery store still relies on manual systems in various operational processes. This causes inefficiencies in inventory management, communication and decision making. Therefore, it is recommended to implement an integrated management system at Queen Bakery to improve operational efficiency, communication, decision making and customer information services. By taking steps to increase employee morale and implementing a more effective management information system, it is hoped that the Queen Bakery store can improve company performance and provide better service to customers. This research contributes to understanding the importance of work morale and management information systems in improving company performance in the food retail sector.